US-Cuba agenda : opportunity or stalemate. - FALK, Pamela S. (1997)
Looks at ways in which the US administration can re-assess its policy towards Cuba and devise a plan of action. Suggests that such a policy should be reliable and be based upon certain fundamental guidelines, which should include: (a) multilateral negotiations on claims issues, accompanied by pressure for a peaceful transition to democracy and increased human rights in Cuba; (b) bilateral negotiations on migration and related issues; (c) increased information link; and (d) licensing of authorised travel.